Strong spin-orbit coupling effects on the Fermi surface of Sr 2 RuO 4 and Sr 2 RhO 4 - Haverkort, Maurits W. (Physical review letters, 2008)
We present a first-principles study of spin-orbit coupling effects on the Fermi surface of Sr2RuO4 and Sr2RhO4. For nearly degenerate bands, spin-orbit coupling leads to a dramatic change of the Fermi surface with respect to nonrelativistic calculations; as evidenced by the comparison with experiments on Sr2RhO4, it cannot be disregarded. For Sr2RuO4, the Fermi surface modifications are more subtle but equally dramatic in the detail: Spin-orbit coupling induces a strong momentum dependence, normal to the RuO2 planes, for both orbital and spin character of the low-energy electronic states. These findings have profound implications for the understanding of unconventional superconductivity in Sr2RuO4.
Die Zahlen "2" und "4" im Titel sind jeweils tiefgestellt
Gesehen am 07.11.2017